Word shortening in Snowdrift Chipewyan - Henry, Dave (University of Calgary, 1980)
In my fieldwork on Chipewyan in Snowdrift, N.W.T. in 1979 it became immediately apparent that variations between speakers were often extensive and that, in particular, younger speakers (roughly, under 30 years old) consistently differed from older speakers and that the variation was greatest between the youngest and the oldest speakers. Yes